CaOx crystal nuclei are formed in rat outer cortex proximal tubules by a potential fibrinogen-dependent mechanism - Kenshirou Kunii; Shigeru Sugiki; Chiharuko Ushimoto; Shinya Inoue; Nobuyo Morita; Yuka Nakamura; Tetsuhiro Horie; Takuya Sakamoto; Hiromi Sakata-Haga; Jia Han; Toshihisa Hatta; Yasuhito Ishigaki; et al. (PLoS ONE, 2025)
Calcium oxalate (CaOx) stones are prevalent in urinary tract stone disease. While their formation can be induced in rats by administering ethylene glycol and vitamin D, the initial nucleation and formation processes are unclear. Here, we aimed to determine where CaOx crystals initially form, examine the associated histological and morphological changes, and clarify the genes whose expression varies at those sites and their function. Male Wistar rats were divided into four groups: control, ethylene glycol, vitamin D, and ethylene glycol plus vitamin D (EG + VitD). Crystal development locations were mapped on kidney tissue sections, and the initial crystal site distribution was revealed. CaOx crystal formation was observed only in the EG + VitD group kidneys, predominantly in the proximal tubules in the outer renal cortex. The tubular luminal area was significantly increased (P < 0.05), especially in proximal tubules, correlating with the crystal occurrence number. Moreover, aquaporin1 and calbindin staining identified the tubular segments hosting initial crystal formation, and the tubular dilation was calculated. DNA microarray was analyzed on cortical and medullary kidney tissues to detect stone formation-related gene expression changes. Genes with variable expression were further examined using RT-PCR and immunohistochemistry to analyze their distribution. FGA, Slc7a9, Slc7a7, and TRPV5 were significantly upregulated in the renal cortex, and FGA was significantly upregulated in the proximal tubules, consistent with the crystal formation sites. Early phase crystallization primarily occurs in the proximal tubules. In silico analysis, FGA protein has multiple oxalic acid-binding sites, making it a potential new factor promoting CaOx crystal formation.